Efeito imunomodulador da inflorescência de Musa paradisiaca linnaeus (Musaceae) na síndrome de asma e rinite alérgicas combinadas (CARAS) dependente da inibição do NF-KB e em macrófagos humanos - Gadelha, Francisco Allysson Assis Ferreira (2020)
A combined allergic asthma and rhinitis syndrome (CARAS) has a common pathophysiology in the upper and lower airways with manifestations of rhinitis symptoms: sneezing, watery eyes, itchy nose with rubbing, nasal congestion and asthma: wheezing, coughing and shortness of breath, which develops concomitantly or separately. The control of the syndrome occurs using clinical protocols for two diseases, however, some patients do not respond adequately and are also compromised by side effects caused by the drugs used. Musa paradisiaca L. (Musaceae), known as a “banana”, grows in the tropical regions of the planet and is used as food. Studies of the plant demonstrate various biological activities, including anti-inflammatory. In Brazil, a banana inflorescence (heart, mangará) is used to control respiratory allergies. For cientific proof of the biological activity of the plant or the immunomodulatory potential for inflorescence extraction (EHM) in the murine model of CARAS analyzing the clinical signs of rhinitis: sneezing and nasal friction, nasal hyper-reactivity induced with histamine, IgE OVA-specific title and percentage of eosinophils in the blood, mucus production in the airways, cell infiltration in the fluid lavage nasal (NALF) and bronchial (BALF) and airway tissue, concentration of cytokines: IL-4, IL -13, IL-5, IL-33, IL-17A, IL-10 and IFN-ɣ in BALF and modulation of the NF-κB. In addition, to the evaluation of CD14, CD86, HLA-DR, CD163 and CD206 receptors in human macrophages exposed to EHM. For this, BALB/c mice were sensitized and challenged with ovalbumin (OVA) and treat, after the challenges, with EHM. The results were analyzed statistically with one-way ANOVA, p<0.05 was considered significant. EHM decreased the clinical signs of rhinitis, nasal hyper-reactivity with histamine, eosinophil-dependent cell infiltrate in NALF and BALF, IgE production, concentrations of cytokines IL-4, IL-13, IL-5 and IL-17A at BALF. In addition, the IFN-ɣ concentration of the Th1 profile increased. In the nasal and pulmonary histological analysis, the EHM promoted an improvement in the tissue architecture of both regions with a decrease in cell infiltrate, goblet cell metaplasia, mucus production, the number of mast cells and the deposition of collagen fibers. The molecular analysis showed that the EHM was able to negatively modulate the activation of the transcription factor NF-κB. Preliminary in vitro studies demonstrate that the EHM decreased the expression of human macrophage receptors (CD86, HLA-DR) involved in their activation and performance in inflammatory processes, as well as decreased the production of IL-6 by these cells. Therefore, we can infer that the inflorescence has antiallergic and immunomodulatory activity, scientifically proven, in the experimental model of CARAS and in exposure to human cells, characterizing it as a potential for the development of herbal medicine for use in allergic diseases of the respiratory tract.